Manufacturing By-Products as Partial Replacement in Metakaolin-Based Geopolymer Mortar Production - Awad, Ashraf Jihad (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
Geopolymer technology is a new, sustainable approach for producing binding materials without using any cement content. Cement production has negative environmental effects in addition to the large amount of energy and nonrenewable resource consumption; therefore, the use of waste-materials is highly valued in geopolymer production. Using waste materials for production has the potential to reduce waste disposal costs and landfills effects on the environment. Within the same context, red mud (RM) is a waste material that is abundantly available in Turkey and around the world. Thus, it is critical to investigate the use of RM and other waste materials that can affect agriculture and groundwater in the construction industry. This study investigates the strength and durability properties of binary and ternary geopolymer mortar composites of metakaolin (MK) and three different waste by-products (RM, rice husk ash, and waste glass powder (GP)), which are abundantly available in Turkey. Further, this dissertation discusses the effects of high temperature on geopolymer mortar properties and the impact of adding two different sizes of glass fibers (GFs) by 0.3% volume to a geopolymer produced using MK and partially replaced by RM and GP. The GFs have been selected due to the cheap price and high flexibility and strength. Moreover, the dissertation explores the strength properties of the produced mortar in sea water and sulphate environments. Finally, the effect of the sand-to-binder (S/B) ratio on the strength and durability properties under different conditions and environments are investigated. The results indicate that the significant strength properties of the geopolymer mortar can be obtained by binary and ternary composites of MK, RM, and GP. The addition of GFs improves the strength properties of the produced mortar; the addition of 12 mm GFs improves the strength more than that using the 6 mm GFs. However, S/B ratio affects the strength properties significantly, and the results indicated that an S/B ratio of 2.5 is better than that of 2.25. The produced geopolymer is applicable under severe conditions such as high temperature, magnesium sulphate, freezing–thawing, and sea water environment.

ÖZ: Jeopolimer teknolojisi, çimento içermeyen bağlayıcı malzemeleri üretmek için yeni ve sürdürülebilir bir yaklaşımdır. Çimento üretiminde tüketilen yüksek miktarda enerji ve yenilenemeyen kaynak tüketiminin yanı sıra, çimento üretiminin çevresel etkileri nedeniyle, jeopolimer üretim yaklaşımında atık malzemelerin kullanılması oldukça değerlidir. Böyle bir yaklaşım, atık bertaraf maliyetlerini ve çöp depolama alanlarının çevre üzerindeki etkilerini azaltma potansiyeline sahiptir. Aynı bağlamda kırmızı çamur, Dünyada ve Türkiye'de çok miktarda bulunan bir atık maddedir. Bu nedenle, inşaat sektöründe tarımı ve yeraltı suyunu etkileyen kırmızı çamur ve diğer atık maddelerin kullanımının araştırılması kritik önem taşımaktadır. Bu çalışma, Türkiye'de önemli miktarlarda bulunan metakaolin ve üç farklı atık yan ürünün (kırmızı çamur, pirinç kabuğu külü ve atık cam tozu) ikili ve üçlü jeopolimer harç kompozitlerinin mukavemet ve dayanıklılık özelliklerini araştırmaktadır. Bu tez ayrıca, jeopolimer harç özellikleri üzerindeki yüksek sıcaklık etkilerini ve kısmen kırmızı çamur ve atık cam tozu ile değiştirilen metakaolin tarafından üretilen bir jeopolimere iki farklı boyutta cam elyafı eklemenin etkisini tartışır. Ayrıca, yapılan harcın deniz suyu ve sülfat ortamlarındaki dayanım özelliklerini araştırır. Son olarak, bu çalışmada kum/bağlayıcı oranının farklı koşullar ve ortamlarda dayanım ve dayanıklılık özellikleri üzerindeki etkileri araştırılmıştır. Genel olarak sonuçlar, metakaolin, kırmızı çamur ve atık cam tozunun ikili ve üçlü kompozitleri ile jeopolimer harcın önemli mukavemet özelliklerinin elde edilebileceğini göstermiştir. Ayrıca cam elyaf ilavesi üretilen harcın mukavemet özelliklerini iyileştirir; 12 mm uzunluk boyutu, gücü 6 mm'den fazla artırır. Ancak kum/bağlayıcı oranı dayanım özelliklerini önemli ölçüde etkiler ve sonuçlar 2.5 oranının 2.25'ten daha iyi olduğunu göstermiştir. Ayrıca, üretilen jeopolimer, yüksek sıcaklık, magnezyum sülfat, donma-çözülme ve deniz suyu gibi dayanıklılık koşullarında uygulanabilmektedir.
Doctor of Philosophy in Civil Engineering. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2021. Co-Supervisor: Assoc. Prof. Dr. Beste Çubukçuoğlu and Supervisor: Assoc. Prof. Dr. Tülin Akçaoğlu.
Keywords: Civil Engineering Department; Aggregates (Building materials)--Concrete; Construction Engineering--Supplementary Cementitious Materials; Cement composites; Composite materials; Building materials; Inorganic polymers; Geopolymer, geopolymer mortar, sustainability, waste materials, strength properties, by-products, glass fiber